Reproductive and Morphological Quality of Commercial Honey Bee (Hymenoptera: Apidae) Drones in the United States. Issue 6 (1st November 2021) - Metz, Bradley N; Tarpy, David R
Abstract: Exploration into reproductive quality in honey bees ( Apis mellifera Linneaus (Hymenoptera: Apidae) largely focuses on factors that affect queens, with drones primarily being considered insofar as they pass on effects of environmental stressors to the queen and subsequent offspring. In those studies that consider drone quality explicitly, a primary focus has been on the dimorphic nature of drones laid in worker cells (either through rare queen error or worker reproduction) as compared to drones laid by the queen in the slightly larger drone cells. The implication from these studies is that that there exists a bimodality of drone morphological quality that is related to reproductive quality and competitive ability during mating. Our study quantifies the presence of such small drones in commercial populations, finding that rates of 'low-quality' drones are far higher than theoretically predicted under optimum conditions. Observations from commercial colonies also show significant inter-colony variation among the size and fecundity of drones produced, prompting speculation as to the mechanisms inducing such variation and the potential use of drone-quality variation for the colony- or apiary-level exposure to nutrition, agrichemical, or parasitic stressors.